2023
DOI: 10.1002/vjch.202200128
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of TiO2‐doped carbon aerogel from sugarcane bagasse for high efficiency of photodegradation of methylene blue in the water

Tong Hoang Lin,
Tran Quoc Thang,
Hoang An
et al.

Abstract: In this work, TiO2‐doped carbon aerogel (TiO2/CA) was synthesized from sugarcane bagasse hydrothermal, freeze‐drying, and carbonization methods. The effects of the calcination temperatures of 400, 500, 600, 700, and 800 °C were also evaluated. The obtained TiO2/CA exhibits an ultralow density (0.021‐0.032 g/cm3) and porosity of more than 97 %. The as‐prepared TiO2/CA was applied in photodegradation of methylene blue (MB) with the effects of dose sample and pH were also investigated. The results show that TiO2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The sample after impregnation contains silica, titania and oxygen which have different roles because silica with a large surface area increases the homogenization process of methylene blue on the silica surface during the dark adsorption process while titania acts as an active center for photodegradation. The band gap of TiO2 in subsequent studies is approximately 3.3 eV [37] and changed after incorporation in SiO2 to 3.21 eV [38], which is the material for confirming the cause of faster degradation in the presence of UV light compared to the material without a photocatalyst under UV light irradiation, which indicates that the SiO2 material without TiO2 only adsorbs methylene blue [39]. Initial rate estimates demonstrated that the first 30 min of Table 2.…”
Section: Resultsmentioning
confidence: 73%
“…The sample after impregnation contains silica, titania and oxygen which have different roles because silica with a large surface area increases the homogenization process of methylene blue on the silica surface during the dark adsorption process while titania acts as an active center for photodegradation. The band gap of TiO2 in subsequent studies is approximately 3.3 eV [37] and changed after incorporation in SiO2 to 3.21 eV [38], which is the material for confirming the cause of faster degradation in the presence of UV light compared to the material without a photocatalyst under UV light irradiation, which indicates that the SiO2 material without TiO2 only adsorbs methylene blue [39]. Initial rate estimates demonstrated that the first 30 min of Table 2.…”
Section: Resultsmentioning
confidence: 73%